Disproportionality evaluation of adverse effects and suicide/self-injury risk factors associated with vortioxetine: a large-scale pharmacovigilance study - Li, Xiangyu; Yang, Fang; Yuan, Lingjing; Ma, Li (Frontiers in Pharmacology, 2025)
IntroductionAdverse events associated with antidepressants may contribute to stigma, morbidity, and suicidal behaviour among patients. Effectively assessing the risk of potential AEs induced by antidepressants is crucial for guiding treatment strategy selection. In this study, the antidepressant-related AEs of vortioxetine and other antidepressants were analysed using data from the FDA Adverse Event Reporting System (FAERS) and the Japanese Adverse Drug Event Report (JADER), with a particular focus on the risk factors for suicide and selfinjury events.MethodsDemographic data, adverse events types, and frequencies for patients using vortioxetine were summarized from the FDA Adverse Event Reporting System and Japanese Adverse Drug Event Report database, covering the third quarter of 2013 to the third quarter of 2024, through data cleaning, analysis, and statistical methods. The risk signals were identified using four disproportionality methods.ResultsThere were 13,097 and 509 AE reports listing vortioxetine as the “primary suspect” from the FAERS and JADER, respectively. Twenty-seven system organ classes and 2002 preferred terms (PTs) signals were identified, and vortioxetine JADER with 25 SOCs (218 PTs). Notable differences existed in the signal strength values obtained for identical PTs from the two databases. More than 20 novel AEs, not listed on the product label, were identified. Notably, stronger correlations for suicide/self-injury were observed for vortioxetine via multivariate logistic regression analysis. Additionally, compared with their male counterparts, female patients are significantly more susceptible to suicide/self-injury. The risk of suicide/self-injury was significantly lower in individuals aged ≥25 years than in those aged 0–24 years (p < 0.05), and the lowest risk was found in patients aged ≥60 years (OR 0.26 (0.22–0.30), p < 0.001).DiscussionThe detected risk signals indicate only the statistical correlation between the target drug and the target adverse reaction and do not indicate the inevitable causal link between the drug and adverse response. Likely confounders include vortioxetine’s preferential prescription in complex patient populations (attributed to its broad-spectrum efficacy and safety profile) rather than intrinsic drug effects. Future studies should consider controlling for these confounders to provide a more definitive assessment.